Characterization and Management of Hedgehog Pathway Inhibitor-Related Adverse Events in Patients With Advanced Basal Cell Carcinoma. (10th August 2016) - Lacouture, Mario E.; Dréno, Brigitte; Ascierto, Paolo Antonio; Dummer, Reinhard; Basset-Seguin, Nicole; Fife, Kate; Ernst, Scott; Licitra, Lisa; Neves, Rogerio I.; Peris, Ketty; Puig, Susana; Sokolof, Jonas; et al.
Abstract : Abnormal activation of hedgehog pathway signaling is a key driver in the pathogenesis of basal cell carcinoma (BCC). Vismodegib, a first-in-class small-molecule inhibitor of hedgehog pathway signaling, is approved by regulatory authorities for the treatment of adults who have metastatic BCC or locally advanced BCC that has recurred after surgery, or who are not candidates for surgery and who are not candidates for radiation. A second inhibitor, sonidegib, was also recently approved for the same patient group with locally advanced BCC. Adverse events (AEs) commonly observed in hedgehog pathway inhibitor (HPI)-treated patients include muscle spasms, ageusia/dysgeusia, alopecia, weight loss, and asthenia (fatigue). These AEs are thought to be mechanistically related to inhibition of the hedgehog pathway in normal tissue. Although the severity of the majority of AEs associated with HPIs is grade 1–2, the long-term nature of these AEs can lead to decreased quality of life, treatment interruption, and in some cases discontinuation, all of which might affect clinical outcome. The incidence, clinical presentation, putative mechanisms, and management strategies for AEs related to HPIs in advanced BCC are described. These observations represent the first step toward the development of mechanism-based preventive and management strategies. Knowledge of these AEs will allow health care professionals to provide appropriate counseling and supportive care interventions, all of which will contribute to improved quality of life and optimal benefit from therapy. Abstract : Vismodegib and sonidegib are Hedgehog pathway inhibitors (HPIs) approved for treatment of patients with advanced basal cell carcinoma. The adverse events (AEs) associated with these therapies can impact clinical outcomes as a result of decreased quality of life and treatment discontinuation. The incidence, clinical presentation, putative mechanisms, and management strategies for AEs related to administration of HPIs are described in this article.